Heterogeneous conducting membrane catalyst for photocatalytic coenzyme regeneration and preparation method thereof
The heteroconducting membrane photocatalyst of microcapsule structures is prepared by regulating the ratio of amino monomers, which solves the problem of mismatch between electrons and proton transfer in photocatalytic coenzyme NADH regeneration, and achieves efficient and stable NADH regeneration performance.
Patent Information
- Application Number
- CN202411801020.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-09
AI Technical Summary
In the existing photocatalytic coenzyme NADH regeneration technology, the electron and proton transfer rates are mismatched, resulting in low electron utilization efficiency and the selectivity and initial reaction rate of the NADH regeneration process.
By regulating the ratio of amino monomer m-Bpy and m-PaHSO3 during the synthesis process, a heteroconducting membrane photocatalyst with a series of microcapsule structures was prepared to optimize electron and proton transfer behaviors, thereby matching electron and proton transfer during photocatalysis.
The photocatalytic coenzyme NADH regeneration process is achieved efficiently and stably, significantly improving the NADH regeneration performance, and improving electron utilization efficiency and proton transfer efficiency.
Smart Images

Figure CN119608237A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the preparation of photocatalysts, and in particular to a high-efficiency catalyst for photocatalytic coenzyme regeneration and a preparation method thereof Background Art
[0002] Green biomanufacturing is a process that uses enzymes or microorganisms to process target products through chemical engineering technology with biotechnology as the core. It is a typical new quality productivity that can help transform traditional industries, reduce industrial energy consumption by 15%, and reduce air and water pollution by about 30%. Vigorously developing green biomanufacturing technology is an important support for solving energy, resource and environmental crises and achieving sustainable development. Industrial enzyme catalysis is a typical green biomanufacturing technology, of which redox enzyme catalysis accounts for about 25%, and most of them rely on nicotinamide coenzymes (such as NADH) to provide reducing power. However, the price of NADH per mole is about 5 million yuan, which to a certain extent limits the industrial application of enzyme catalysis. To this end, researchers have developed various types of coenzyme regeneration systems driven by chemical energy, electrical energy, light energy, etc. Among them, the use of clean, abundant and renewable solar energy for photocatalytic coenzyme regeneration has the advantages of clean energy source, environmental friendliness and controllable process.
[0003] The light-driven coenzyme NADH regeneration process mainly uses organic molecules such as triethanolamine as electron donors and semiconductors as photocatalysts. Visible or ultraviolet light is used to irradiate semiconductors to generate photogenerated electrons and holes. Triethanolamine captures holes, and photogenerated electrons are transferred to the reduction site for NAD + to NADH. + The photocatalytic conversion of NAD to NADH involves the transfer of two electrons and one proton. The faster electron-hole recombination causes the electrons to be quenched prematurely, making it difficult to ensure that more photogenerated electrons are transferred to the reduction active sites, thus reducing the electron utilization efficiency of the NADH regeneration process. + The efficiency of binding with protons affects the 1,4-NADH selectivity and initial reaction rate during the regeneration process.
[0004] Therefore, the variable monomer ratio in HCM preparation was used to regulate the electron and proton transfer behaviors in the photocatalytic process. At the optimal ratio of m-Bpy and m-PaHSO3, the electron and proton transfer processes in photocatalysis were matched, achieving efficient and stable regeneration of the coenzyme NADH. Summary of the invention
[0005] The purpose of the present invention is to provide a catalyst for photocatalytic coenzyme regeneration and a preparation method thereof. The raw materials for the preparation of the present invention are cheap and easily available, and the preparation process is simple and easy.
[0006] The present invention provides a method for preparing a heterogeneous conductive film photocatalyst for photocatalytic coenzyme regeneration, comprising the following steps:
[0007] Step 1. Prepare silica particles modified with polyethyleneimine and dopamine: mix silica balls with a polyethyleneimine aqueous solution and a dopamine aqueous solution to obtain liquid A, wherein the mass-to-volume ratio of the silica balls in liquid A is 1 g / 100 mL, and the mass ratio of the silica balls, polyethyleneimine and dopamine is 1:2:2. Under a magnetic stirrer, stir liquid A in a sealed and perforated state to obtain suspension A; centrifuge the suspension A, wash it with water, and dry it to obtain silica particles modified with polyethyleneimine and dopamine.
[0008] Step 2: preparing core-shell particles, comprising:
[0009] 2-1) At room temperature, the particles obtained in step 1 are used as template particles. In a three-necked flask, 500 mg of the template particles are mixed with 1 mol of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine monomer (m-TFPT) and tetrahydrofuran (THF) to obtain liquid B, wherein the molar concentration of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine monomer and tetrahydrofuran in liquid B is 1 mol / 110 mL; 6 mol / L acetic acid solution is added to solution B at a volume ratio of 1:110, and liquid C is obtained after hydrothermal reflux reaction under a magnetic stirrer;
[0010] 2-2) using tetrahydrofuran as solvent, dissolving 2,4,6-tris(4-formylphenyl)-1,3,5-triazine monomer (m-TFPT), 5,5'-diamino-2,2'-bipyridine monomer (m-Bpy) and 2,5-diaminobenzenesulfonic acid monomer (m-PaHSO3) in an appropriate amount of tetrahydrofuran at a molar ratio of N1:N2:N3=2:(1-3):(0-2), and N1+N2+N3=5, to obtain liquid D;
[0011] 2-3) According to the volume ratio of liquid D to liquid C being 4:11, liquid D is added to liquid C at an amount of 1 / 10 of liquid D per minute, and suspension B is obtained after hydrothermal reflux. The suspension B is centrifuged and washed with tetrahydrofuran, and then dried to obtain core-shell particles.
[0012] Step 3, preparation of heterogeneous conductive film photocatalyst: add the core-shell particles obtained in step 2 to a 6 mol / L ammonium bifluoride solution at a mass volume ratio of 7-10 mg / mL, stir thoroughly to obtain suspension C, centrifuge and wash the suspension C with water, and dry to obtain microcapsule structured particles, which are the heterogeneous conductive film photocatalyst.
[0013] Furthermore, the preparation method of the present invention, wherein:
[0014] In step 1, the diameter of the silicon oxide spheres is 300-500nm; the stirring speed of the magnetic stirring is 600-800r / min, and the stirring time is 4h; the speed of the centrifugal water washing is 8000-10000r / min, and the time is 4-5min; the drying temperature is 40°C, and the time is 24h.
[0015] In step 2-1), the process conditions of the hydrothermal reflux reaction under a magnetic stirrer are: the stirring speed of the magnetic stirrer is 120 r / min, the reaction time of the hydrothermal reflux is 30 min, and the temperature of the hydrothermal reflux is 50°C.
[0016] In step 2-2), N1:N2:N3 is any one of 2:3:0, 2:1:2, and 2:2:1, and preferably, N1:N2:N3 is 2:2:1.
[0017] In step 2-3), liquid D is added to liquid C, and the hydrothermal reflux time is 48 hours; the suspension B is washed by centrifugation with tetrahydrofuran three times at a speed of 8000-10000 r / min, each time for 5 minutes; the drying temperature is 70°C, and the drying time is 12 hours.
[0018] In step three, the time for sufficient stirring is 24 hours; the suspension C is centrifuged and washed with water for 3 times, the speed is 8000-10000r / min, each time is 5 minutes, and the drying temperature after centrifugal washing is 70°C, and the drying time is 12 hours.
[0019] For the convenience of description, in the embodiments of the present invention, the ratio of the amino monomers (m-Bpy and m-PaHSO3) used is different, and the heterogeneous conductive film photocatalysts with microcapsule structures finally obtained are respectively recorded as:
[0020] The molar ratio of m-TFPT to m-Bpy to m-PaHSO3 is 2:3:0, and the resulting heterogeneous conductive film photocatalyst with microcapsule structure is referred to as HCM. BS30 .
[0021] The molar ratio of m-TFPT to m-Bpy to m-PaHSO3 is 2:2:1. The heterogeneous conductive film photocatalyst with microcapsule structure obtained is referred to as HCM. BS21 .
[0022] The molar ratio of m-TFPT to m-Bpy to m-PaHSO3 is 2:1:2. The heterogeneous conductive film photocatalyst with microcapsule structure obtained is referred to as HCM. BS12 .
[0023] Compared with the prior art, the preparation method of the heterogeneous conductive film photocatalyst for photocatalytic coenzyme regeneration proposed in the present invention uses the ratio of monomers in the catalyst synthesis process to regulate the electron and proton transfer behavior in photocatalysis for the first time. This method can effectively solve the problem of mismatch between the electron and proton transfer rates in photocatalytic coenzyme regeneration, thereby improving the photocatalytic coenzyme regeneration performance. The preparation method of the present invention has mild conditions and simple process. Compared with the existing photocatalytic coenzyme regeneration technology, the system photocatalyst with different amino monomer ratios (m-Bpy and m-PaHSO3) prepared in the present invention has a significant improvement in the performance of coenzyme regeneration. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1a ) is the HCM prepared in Example 1 of the present invention BS30 TEM photos of
[0025] Figure 1b ) is the HCM prepared in Example 2 of the present invention BS21 TEM photos of
[0026] Figure 1c ) is the HCM prepared in Example 3 of the present invention BS12 TEM photos of
[0027] Figure 2 HCM prepared in Examples 1-3 of the present invention BS30 , HCM BS21 and HCM BS12 Time-resolved fluorescence spectra of
[0028] Figure 3 HCM prepared in Inventive Examples 1-3 BS30 , HCM BS21 and HCM BS12 The proton conductivity of
[0029] Figure 4 HCM prepared in Inventive Examples 1-3 BS30 , HCM BS21 and HCM BS12 NADH yield for photocatalytic coenzyme regeneration. DETAILED DESCRIPTION
[0030] The design idea of a heterogeneous conductive film photocatalyst for photocatalytic coenzyme regeneration proposed by the present invention is: after growing an organic polymer coating on a silicon oxide surface by a hard template method, the template is removed to obtain a photocatalyst HCM with a microcapsule membrane structure based on a covalent organic polymer. In the process of growing the covalent organic polymer coating, the amount of an aldehyde monomer (m-TFPT) is fixed unchanged, and by adjusting the ratio of the other two amino monomers (m-Bpy and m-PaHSO3), a series of heterogeneous conductive film photocatalysts with microcapsule structures having different amino monomer ratios (m-Bpy and m-PaHSO3) are prepared by utilizing the adjustable monomer ratio characteristics during the coating growth process. The contents of the two amino monomers m-Bpy and m-PaHSO3 used in the coating formation process will affect the electron and proton transfer problems of the photocatalyst in the photocatalytic process. More m-Bpy is conducive to electron transfer, while correspondingly less m-PaHSO3 is not conducive to proton transfer. Photocatalytic coenzyme regeneration involves the transfer and utilization of two electrons and one proton. By coordinating the content of m-Bpy and m-PaHSO3, the effect of coordinating the transfer of electrons and protons in the photocatalytic process is achieved. The optimal monomer ratio has the optimal electron and proton transfer behavior, which is beneficial to NAD + The conversion to NADH ultimately achieves the enhancement of the photocatalytic coenzyme NADH regeneration process.
[0031] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The described specific embodiments are only used to explain the present invention and are not intended to limit the present invention.
[0032] Example 1: HCM with microcapsule structure BS30 Preparation and HCM-based BS30 The photocatalytic coenzyme NADH regeneration system is constructed, and the steps are as follows:
[0033] Step 1: Preparation of polyethyleneimine and dopamine modified silicon oxide particles:
[0034] 1 g of silica balls (with a diameter of 300-500 nm) prepared at room temperature was mixed with a polyethyleneimine aqueous solution and a dopamine aqueous solution in a mass ratio of about 1:1 under a magnetic stirrer at a stirring speed of 800 r / min. The mixed solution was stirred at a stirring speed of 800 r / min for 4 hours in a sealed and perforated state. The obtained suspension was centrifuged in a centrifuge (speed 9000 r / min, time 5 min), washed with water 3 times, and dried at 40°C for 24 hours to obtain modified template particles, referred to as SiPP.
[0035] Step 2: Preparation of core-shell particles:
[0036] At room temperature, a certain amount of modified template particles SiPP and 0.1 mol of m-TFPT were weighed and mixed with 11 mL of tetrahydrofuran solvent in a three-necked flask, and 100 μL of 6 mol / L acetic acid solution was added. Under a magnetic stirrer, the stirring speed was 120 r / min, and the hydrothermal reflux reaction temperature was 50°C. After reacting for 30 minutes, m-Bpy with a molar ratio of 3:2 to m-TFPT was dissolved in 4 mL of tetrahydrofuran solvent and added to the above three-necked flask in an amount of 1 / 10 per minute. After hydrothermal reflux for 48 hours, the obtained suspension was centrifuged in a centrifuge (speed 10000 r / min, time 5 minutes), washed with tetrahydrofuran 3 times, and dried at 70°C for 12 hours to obtain core-shell particles, referred to as SiPP@HCM. BS30 Particles.
[0037] Step 3: Preparation of HCM microcapsule structure BS30 :
[0038] Weigh 80 mg of the above SiPP@HCM BS30 The particles were added to 8 mL of 6 mol / L ammonium bifluoride solution and stirred for 24 h. The suspension was centrifuged (speed 10000 r / min, time 5 min) and washed with water three times. The suspension was dried at 70 °C for 12 h to obtain microcapsule-structured HCM. BS30 Particles.
[0039] The prepared photocatalyst HCM BS30 The electron lifetime was detected by time-resolved fluorescence spectroscopy and the proton conductivity was detected by electrochemical means, and then used in the coenzyme regeneration system. The process was carried out in phosphate buffer. The reaction solution contained triethanolamine as an electron donor, a rhodium complex as a reduction reaction active center, and HCM BS30 As a photocatalyst, NAD + As a substrate, 420nm LED lamp is used to provide light energy to achieve efficient photosynthesis of NADH.
[0040] Figure 1a ) is HCM BS30 TEM image shows that it is a microcapsule membrane structure with a thickness of 35 nm; Figure 2 The middle (shown in black) shows the HCM BS30 The electron lifetime is 374ps; Figure 3 HCM is shown BS30 The proton conductivity is 11.5 mS cm -1 ; Figure 4 The middle (shown in black) shows the HCM BS30 Used in the photocatalytic NADH regeneration process, the NADH yield was 83%.
[0041] Example 2: HCM with microcapsule structureBS21 Preparation and HCM-based BS21 The photocatalytic coenzyme NADH regeneration system was constructed, and the steps were basically the same as those in Example 1, except that in step 2, m-Bpy with a molar ratio of 3:2 to m-TFPT was replaced with m-Bpy with a molar ratio of 1:1 to m-TFPT and m-PaHSO3 with a molar ratio of 1:2 to m-TFPT, and finally a microcapsule structured HCM was prepared. BS21 Particles.
[0042] Figure 1b ) is HCM BS21 TEM image shows that it is a microcapsule membrane structure with a thickness of 38 nm; Figure 2 The HCM is shown in red. BS21 The electron lifetime is 229ps; Figure 3 HCM is shown BS21 The proton conductivity is 63.4 mS cm -1 ; Figure 4 The HCM is shown in red. BS21 Used in photocatalytic NADH regeneration process, the NADH yield is 90%.
[0043] Example 3: HCM with microcapsule structure BS12 Preparation and HCM-based BS12 The photocatalytic coenzyme NADH regeneration system was constructed, and the steps were basically the same as those in Example 1, except that in step 2, m-Bpy with a molar ratio of 3:2 to m-TFPT was replaced with m-Bpy with a molar ratio of 1:2 to m-TFPT and m-PaHSO3 with a molar ratio of 1:1 to m-TFPT, and finally a microcapsule structured HCM was prepared. BS12 Particles.
[0044] Figure 1c ) is HCM BS12 TEM image shows that it is a microcapsule membrane structure with a thickness of 30 nm; Figure 2 The HCM is shown in the middle (shown in blue) BS12 The electron lifetime is 145ps; Figure 3 HCM is shown in BS12 The proton conductivity is 170.8 mS cm -1 ; Figure 4 The HCM is shown in the middle (shown in blue) BS12 Used in the photocatalytic NADH regeneration process, the NADH yield was 84%.
[0045] In summary, through the above examples and comparative examples and their corresponding TEM images, it is found that by changing the amino monomer during the synthesis process, a microcapsule membrane structure with adjustable thickness is obtained. The amount of aldehyde monomer is fixed and the ratio of the two aldehyde monomers is changed. The synthesized HCM has different electron and proton transfer behaviors. The higher the ratio of m-Bpy, the more conducive it is to electron transfer. Therefore, from the time-resolved fluorescence spectrum, it can be seen that HCM BS30 (374ps) showed a better performance than HCM BS21 (229ps) and HCM BS12 (145ps) longer electron lifetime, such as Figure 2 As shown; HCM BS12 (170.8mS cm -1 ) showed a better performance than HCM BS21 (63.4mS cm -1 ) and HCM BS30 (11.5mS cm -1 ) better proton conductivity, such as Figure 3 As shown in the figure. The photocatalytic coenzyme NADH regeneration process involves the participation of two electrons and one proton. The rapid electron-hole recombination causes the electrons to be quenched prematurely, making it difficult for the available photogenerated electrons to be transferred to the reduction active site, thus reducing the electron utilization efficiency. At the same time, proton transfer affects the NAD + The efficiency of combining with protons seriously affects the selectivity and initial reaction rate of the generated 1,4-NADH. To obtain the optimal NADH regeneration efficiency, it is necessary to adjust the electron and proton transfer to match. Therefore, in the present invention, the ratio of monomers affecting electron and proton transfer is adjusted, and the optimal electron and proton transfer rate is obtained when the ratio of amino monomers m-Bpy and m-PaHSO3 is 2:1, so that the NADH regeneration performance is effectively improved. Figure 4 shown.
[0046] Although the present invention has been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can make many improvements and changes without departing from the purpose of the present invention, which are all within the protection of the present invention.
Claims
1. A method for preparing a heterogeneous conductive film photocatalyst for photocatalytic coenzyme regeneration, characterized in that: The following steps are involved: Step 1: Preparation of polyethyleneimine and dopamine modified silicon oxide particles: Silica balls, polyethyleneimine aqueous solution and dopamine aqueous solution are mixed to obtain liquid A, wherein the mass volume ratio of the silica balls in liquid A is 1 g / 100 mL, and the mass ratio of the silica balls, polyethyleneimine and dopamine is 1:2:
2. Liquid A is magnetically stirred in a sealed and perforated state under a magnetic stirrer to obtain suspension A; The suspension A is centrifuged and washed with water, and then dried to obtain silicon oxide particles modified with polyethyleneimine and dopamine; Step 2: preparing core-shell particles, comprising: 2-1) At room temperature, using the particles obtained in step 1 as template particles, in a three-necked flask, 500 mg of the template particles are mixed with 1 mol of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine monomer and tetrahydrofuran to obtain liquid B, wherein the molar concentration of 2,4,6-tris(4-formylphenyl)-1,3,5-triazine monomer and tetrahydrofuran in liquid B is 1 mol / 110 mL; 6 mol / L acetic acid solution is added to solution B at a volume ratio of 1:110, and liquid C is obtained after hydrothermal reflux reaction under a magnetic stirrer; 2-2) using tetrahydrofuran as solvent, dissolving 2,4,6-tris(4-formylphenyl)-1,3,5-triazine monomer, 5,5'-diamino-2,2'-bipyridine monomer and 2,5-diaminobenzenesulfonic acid monomer in an appropriate amount of tetrahydrofuran at a molar ratio of N1:N2:N3=2:(1-3):(0-2), and N1+N2+N3=5, to obtain liquid D; 2-3) adding liquid D to liquid C at a volume ratio of 4:11 at a rate of 1 / 10 of liquid D per minute, obtaining suspension B after hydrothermal reflux, washing suspension B with tetrahydrofuran by centrifugation, and drying to obtain core-shell particles; Step 3: Preparation of heterogeneous conductive film photocatalyst: The core-shell particles obtained in step 2 are added to a 6 mol / L ammonium bifluoride solution at a mass volume ratio of 7-10 mg / mL, and the suspension C is obtained after sufficient stirring. The suspension C is centrifuged and washed with water, and the microcapsule structure particles are obtained after drying, which are the heterogeneous conductive film photocatalyst.
2. The preparation method according to claim 1, characterized in that: In step 2-2), N1:N2:N3 is any one of 2:3:0, 2:1:2, and 2:2:
1.
3. The preparation method according to claim 1, characterized in that: In step 2-2), in step 2-2), N1:N2:N3 is 2:2:
1.
4. The preparation method according to claim 1, characterized in that: In step 1, the diameter of the silicon oxide spheres is 300-500nm; the stirring speed of the magnetic stirring is 600-800r / min, and the stirring time is 4h; the speed of the centrifugal water washing is 8000-10000r / min, and the time is 4-5min; the drying temperature is 40°C, and the time is 24h.
5. The preparation method according to claim 1, characterized in that: In step 2-1), the process conditions of the hydrothermal reflux reaction under a magnetic stirrer are: the stirring speed of the magnetic stirrer is 120 r / min, the reaction time of the hydrothermal reflux is 30 min, and the temperature of the hydrothermal reflux is 50°C.
6. The preparation method according to claim 1, characterized in that: In step 2-3), liquid D is added to liquid C, and the hydrothermal reflux time is 48 hours; the suspension B is washed by centrifugation with tetrahydrofuran three times at a speed of 8000-10000 r / min, each time for 5 minutes; the drying temperature is 70°C, and the drying time is 12 hours.
7. The preparation method according to claim 1, characterized in that: In step three, the time for sufficient stirring is 24 hours; the suspension C is centrifuged and washed with water for 3 times, the speed is 8000-10000r / min, each time is 5 minutes, and the drying temperature after centrifugal washing is 70°C, and the drying time is 12 hours.
8. A heterogeneous conductive film photocatalyst for photocatalytic coenzyme regeneration, characterized in that: Prepared according to the preparation method described in claims 1-7.
Citation Information
Patent Citations
Photocatalyst with magnetic nanocapsule structure and preparation method and application of photocatalyst
CN102658178A
Preparation method and application of nano platinum in-situ modified three-dimensional hollow covalent triazine polymer
CN116273171A
Catalyst with heterostructure of organic zinc complex and molybdenum sulfide as well as preparation method and application of catalyst
CN116273180A
Hydrogen bond organic framework microcapsule membrane as well as preparation method and application thereof
CN118344643A
Integrated catalyst for coenzyme regeneration and preparation method thereof
CN118491564A